India's trade performance during the pre and wto period - Sheela, A.M.; Ramani Mabel (university of Jaffna, 2014)
Economic liberalisation in the early 1990's and implementation of the provisions of the WTO after 2004, have had far reaching consequences for India. While it did spur economic growth, as far as trade was concerned India was moving from a controlled trade regime with restrictions on the exchange rate of the rupee. In this study an attempt has been made to examine India's trade performance both with respect to exports and imports to the major trading regions of the world, viz., the EU, North America, Asia, the Gulf region, Japan and Australia. In addition to growth rates, a Markov model has been fitted to study the dynamics of India's exports and imports. Overall India's trade performance against its trading partners has been very small and has not progressed much after the WTO regime . India's share of trade has concentrated on the Gulf countries with share of 6.82 percent of the exports and 9.56 percent of the imports mainly accounted for by oil. From the results it could be seen that India's share of imports for Australia has increased quite substantially in recent years. Barring trade with the EU and North America, the trade deficit were large particularly with Australia (68%) and the Gulf (42%) counties. Overall while trade grew at the rate of about 8 percent in the pre-WTO period and it increased to around 19 percent per annum in the WTO regime. It is noteworthy that trade growth to Asia and Japan which was low in the pre WTO era grew significantly in the WTO period. Export market stability was witnessed with EU, North America and the Gulf countries as indicated by the Markov chain analysis. So far as imports from India were concerned, most of the countries including Asia and Japan were dependable suppliers. This goes to show a degree of ad hocism with regard to export strategy, which does not augur well for the development of exports from India in the long run, calling for a stable export policy for the Country. Further, a policy to boost exports and reverse the current account deficit is the need of the hour, else it could have far reaching effects on the economy and exchange rate of the Rupee.
Keywords: Economic liberalisation; Gulf countries; Exports and imports